Cost-Effectiveness Analysis of Five Systemic Treatments for Unresectable Hepatocellular Carcinoma in China: An Economic Evaluation Based on Network Meta-Analysis - Zhao, Mingye; Pan, Xingming; Yin, Yue; Hu, Hongfei; Wei, Jifu; Bai, Zhaoshi; Tang, Wenxi (Frontiers in Public Health, 2022)
Background and objective: Unresectable hepatocellular carcinoma (uHCC) is the main histological subtype of liver cancer, and causes great disease burden in China. We aimed to evaluate the cost-effectiveness of five first-line systemic treatments newly approved in Chinese market for the treatment of unresectable hepatocellular carcinoma, sorafenib, lenvatinib, donafenib, sintilimab plus bevacizumab (D+A), and atezolizumab plus bevacizumab (T+A) from the perspective of China’s healthcare system, to provide a basis for decision-making. Methods: We constructed a network meta-analysis of 4 clinical trials and used fractional polynomial models to indirectly compare the effectiveness of treatments. The partitioned survival model was used for cost-effectiveness analysis. Primary model outcomes included the costs in US dollars and health outcomes in quality-adjusted life-years (QALYs) as well as the incremental cost-effectiveness ratio (ICER) under a willingness-to-pay threshold of 33,521 (3 times the per capita gross domestic product in China) per QALY. We performed deterministic and probabilistic sensitivity analyses to investigate the robustness. To test the effect of active treatment duration on the conclusions, we performed a scenario analysis. Results: Compared with sorafenib, lenvatinib, donafenib, D+A, and T+A regimens yielded an increase of 0.25, 0.30, 0.95 and 1.46 life-years, respectively. Correspondingly, these four therapies yielded an additional 0.16, 0.19, 0.51, and 0.86 quality-adjusted life-years (QALYs) and all four incremental cost-effectiveness ratios (ICERs)，40,582.14/QALY gained, 27,601.51/QALY gained, 51,882.40/QALY gained, and 130,502.71/QALY, were higher than 33,521 except for donafenib. T+A was the most effective treatment and donafenib was the most economical option. The sensitivity and scenario analysis results showed that the base-case analysis was highly reliable. Conclusion: Although combination therapy could greatly improve uHCC patient survival benefits, under the current WTP, donafenib is still the most economical option.